2015
DOI: 10.3960/jslrt.55.163
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Severe Diffuse Alveolar Hemorrhage after Bortezomib Administration Suggestive of Pulmonary Involvement of Myeloma Cells

Abstract: Severe acute lung injury is a rare but life-threatening complication associated with bortezomib. We report a patient with multiple myeloma who developed a severe diffuse alveolar hemorrhage (DAH) immediately after the first bortezomib administration. The patient was suspected to have pulmonary involvement of myeloma, which caused DAH after rapidly eradicating myeloma cells in the lungs with bortezomib. Rechallenge with bortezomib was performed without recurrent DAH. In patients with multiple myeloma who manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Alternatively, it has been proposed that metabolites of bortezomib may cause direct injury to the lung [ [13] , [14] , [15] ]. Further, Sugita et al [ 11 ] hypothesized that the alveolar hemorrhage observed in their patient resulted from the rapid disintegration of multiple myeloma cells in the lung following the first dose of bortezomib, and Miyakoshi et al [ 14 ] proposed the same mechanism in one of their patients. However, this mechanism is unlikely to be applicable in our case because, unlike Sugita et al’s patient who had patchy ground glass opacities on CT prior to the initiation of treatment, our patient's initial CT scan had no abnormalities suggestive of leukemic infiltration of the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it has been proposed that metabolites of bortezomib may cause direct injury to the lung [ [13] , [14] , [15] ]. Further, Sugita et al [ 11 ] hypothesized that the alveolar hemorrhage observed in their patient resulted from the rapid disintegration of multiple myeloma cells in the lung following the first dose of bortezomib, and Miyakoshi et al [ 14 ] proposed the same mechanism in one of their patients. However, this mechanism is unlikely to be applicable in our case because, unlike Sugita et al’s patient who had patchy ground glass opacities on CT prior to the initiation of treatment, our patient's initial CT scan had no abnormalities suggestive of leukemic infiltration of the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reports about bortezomib associated pulmonary complications, the mechanism is unclear. 3134 Diarrhea and mucositis of any grade were more frequently reported in the Bor-HDM conditioning regimen. Like previous reports with the Bor-HDM conditioning regimen mucositis and diarrhea were the most commonly reported toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage: In patients presenting with acute onset hypoxia, pulmonary opacities, and fevers, especially in the setting of thrombocytopenia and anemia, pulmonary hemorrhage is a possibility. Diffuse alveolar hemorrhage (DAH) has been rarely reported in MM patients, but there have been cases associated with bortezomib and in the posttransplant setting [2,7,8,120]. Though rare, this is potentially a fatal event.…”
Section: Pulmonarymentioning
confidence: 99%